2D Materials for Skin‐Mountable Electronic Devices. Issue 47 (16th May 2021) - Kim, Jejung; Lee, Yongjun; Kang, Minpyo; Hu, Luhing; Zhao, Songfang; Ahn, Jong‐Hyun
Abstract: Skin‐mountable devices that can directly measure various biosignals and external stimuli and communicate the information to the users have been actively studied owing to increasing demand for wearable electronics and newer healthcare systems. Research on skin‐mountable devices is mainly focused on those materials and mechanical design aspects that satisfy the device fabrication requirements on unusual substrates like skin and also for achieving good sensing capabilities and stable device operation in high‐strain conditions. 2D materials that are atomically thin and possess unique electrical and optical properties offer several important features that can address the challenging needs in wearable, skin‐mountable electronic devices. Herein, recent research progress on skin‐mountable devices based on 2D materials that exhibit a variety of device functions including information input and output and in vitro and in vivo healthcare and diagnosis is reviewed. The challenges, potential solutions, and perspectives on trends for future work are also discussed. Abstract : The unique electrical, mechanical, and optical properties of 2D materials provide a promising route to skin‐mountable electronics, which is necessary for the development of various applications, such as human–machine interfaces and healthcare systems. The recent research progress of skin‐mountable electronics based on 2D materials is reviewed and the challenges and opportunities pertaining to this field are discussed.